Six‐minute screening test can provide valid information about the skills that underlie childhood reading and cognitive abilities. (11th January 2019) - Shamir, Netta; Zivan, Michal; Horowitz‐Kraus, Tzipi
Abstract: Aim: Reading difficulties can have complex origins and diagnostic measures can be expensive and time consuming. We tested Zippy6, a six‐minute screening test that we developed, to see how it compared with a battery of established screening tools. Methods: This study was carried out at Cincinnati Children's Hospital Medical Center, USA, from 2014–2016. We recruited 81 children with reading difficulties and 44 typical readers of six years to 14 years of age (grades 1–8) using advertisements that were placed in healthcare clinics in the community and on hospital announcement boards. The subjects completed a full reading evaluation, which comprised standardised tests and the new Zippy6 screening test. Standard scores from the traditional and Zippy6 tests were compared, and Support Vector Machine learning methods and algorithms were used to examine the results. Results: Significant positive correlations existed between all of the traditional tests and the Zippy6 screening test. The sensitivity and specificity for the ability of the Zippy6 to discriminate between children with reading difficulties and typical readers were both 75%. Conclusion: Using the Zippy6 provided valid information about the skills that underlie reading and cognitive abilities. This screening test could be used by clinicians as either a prediagnostic tool or for postintervention assessment.